Schottky direct-current energy harvesters with large current output density. (August 2019) - Shao, Hao; Fang, Jian; Wang, Hongxia; Niu, Haitao; Zhou, Hua; Cao, Yuying; Chen, Fanyan; Fu, Sida; Lin, Tong
Abstract: Conducting polymer-metal Schottky diodes have emerged as a novel principle for direct conversion of small mechanical forces into direct current (DC) power without rectification. They have great potential in energy harvesting and self-powered miniature electronics. However, it remains a challenge to enhance the electrical outputs through materials design. In this study, we for the first time demonstrate a novel approach to significantly improving the current outputs of Schottky DC generators simply by incorporating a small amount of graphene oxide (GO) into the conducting polymer layer. Using Al/polypyrrole (PPy)/Au as a device model, we show that just adding 1.6 wt% GO into PPy can lead to 525% increase in device current output without changing output voltage. At the optimal condition, the GO involved device can generate peak currents as high as 1.319 A m −2 with an output power density of 0.21 W m −2 . GO is found to play multiple roles in the device, including reducing internal resistance and barrier height at compression state, increasing charge storage and enhancing rectification. Apart from GO, other nano carbons, such as carbon nanotubes and graphene, also show a similar effect on current outputs. This novel approach may be useful for development of various self-powered electronics. Graphical abstract: Image 1 Highlights: Graphene oxide (GO) was added to conducting polymer for making Schottky diode DC generators. Addition of GO can significantly improve the current outputs without alerting device output voltage. GO involved device can generate peak currents as high as 1.319 A m −2 with an output power density of 0.21 W m −2 . Other nano carbons, such as carbon nanotubes and graphene showed similar effect on Schottky diode DC generators.